2010
DOI: 10.1103/physrevb.81.245412
|View full text |Cite
|
Sign up to set email alerts
|

Transport between twisted graphene layers

Abstract: Commensurate-incommensurate transitions are ubiquitous in physics and are often accompanied by intriguing phenomena. In few-layer graphene (FLG) systems, commensurability between honeycomb lattices on adjacent layers is regulated by their relative orientation angle θ, which is in turn dependent on sample preparation procedures. Because incommensurability suppresses inter-layer hybridization, it is often claimed that graphene layers can be electrically isolated by a relative twist, even though they are vertical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(231 citation statements)
references
References 36 publications
8
223
0
Order By: Relevance
“…From a theoretical perspective, twisted bilayer graphene (TBG) has been examined extensively using both continuum [6][7][8][9] and ab-initio [10][11][12][13][14] approaches. These studies have shown that the individual monolayers become significantly decoupled by the rotational faults.…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical perspective, twisted bilayer graphene (TBG) has been examined extensively using both continuum [6][7][8][9] and ab-initio [10][11][12][13][14] approaches. These studies have shown that the individual monolayers become significantly decoupled by the rotational faults.…”
Section: Introductionmentioning
confidence: 99%
“…It is also implicit in Eq. (12) that the top and bottom graphene lattices have a common lattice point [17]; a rigid horizontal translation between lattices adds an additional overall phase to the matrix T j [18]. We stress, however, that relative phases in T j do not alter in any significant way the physics of tunneling in Eq.…”
Section: Model Parametersmentioning
confidence: 98%
“…Indeed, incommensurability between graphene lattices already suppresses interlayer hybridization, regardless of the layer separation being a fraction of a nanometer, thus enabling the sequential tunneling regime [18]. Furthermore, the massless Dirac spectrum, and thus Eq.…”
Section: Other Graphene-based Bistable Systemsmentioning
confidence: 99%
See 2 more Smart Citations